Addressing Health Literacy in Schools in Germany: Concept Analysis of the Mandatory Digital and Media Literacy School Curriculum - Schulenkorf, Tessa; Krah, Verena; Dadaczynski, Kevin; Okan, Orkan (Frontiers in Public Health, 2021)
It is generally agreed upon that the development of health literacy should be addressed from an early age onwards in order to empower children to develop their full health potential. Schools can be seen as an ideal venue for strengthening health literacy because they reach almost all school-aged children throughout their school years. The development of health literacy at a young age is a catalyst for healthy development throughout across the life span. Evidence shows that health and education are intertwined with favorable effects for health (e.g., health behavior, knowledge) and education outcomes (e.g., academic achievement). However, health literacy is often not sufficiently integrated into the school curriculum despite its importance to health and education. Integrating health literacy into schools is challenging, as both schools and teachers already face numerous educational requirements that may prevent them from addressing health that is perceived as an additional task. This is why taking a sensitive approach is important, adapted to the needs of schools and highlighting the benefits of health literacy. Installing health literacy in schools succeeds more easily if it can be linked to existing curricular requirements. In this context, curriculum and instruction on media literacy, information literacy, and digital literacy are most promising subjects to include health literacy because these concepts share many commonalities with health literacy and often are already part of the school curriculum. The aim of this article is to (1) analyze a mandatory curriculum on media literacy in the state of North-Rhine-Westphalia in Germany, (2) highlight its intersections with health literacy, and (3) show how it can be used to address health literacy. The state media literacy framework is based on the federal standards for “digital education” developed by the German Conference on Education Ministries und Cultural Affairs (KMK). As education policy and practice is decentralized with sixteen federal states in Germany, each of them has got their own media literacy framework, or they are currently developing it. This curriculum analysis serves as a methodological blueprint for educationalists, teachers, and policy-maker elsewhere. It may help to integrate health literacy into schools when combined with existing curricula.